Impact of Excipient and Cell Concentration on the Viability, Proliferation, and Adhesion of Mesenchymal Stem Cells: Future Relevance for the Development of a New Advanced Therapy Medicinal Product - Ester Moñivas; Concepción Aguayo; Beatriz Rodera; Mercedes Zurita (Pharmaceutics)
Introduction: The preservation of mesenchymal stem cell (MSC) viability and biological activity is a key aspect in optimizing advanced therapy medicinal products (ATMPs). Evaluating various excipients to optimize MSC conservation and functionality is essential. Methods: Five excipients with different proportions of human platelet lysate (hPL) and Hypothermosol were evaluated at two different cell concentrations (0.1 × 106 MSC/μL and 0.008 × 106 MSC/μL). Cell viability, adhesion, and proliferation capacity were assessed at 24 and 48 h under hypothermic conditions (2–8 °C). Results: A significant interaction was observed between cell concentration and excipient, where the 0.008 × 106 MSC/μL concentration showed better viability results. Excipients with a combination of 50–75% Hypothermosol improved cell viability and adhesion. No significant differences were found in cell proliferation among the excipients studied. Viability, adhesion, and proliferation decreased significantly at 48 h for all excipients and concentrations evaluated. Conclusions: The combination of hPL and Hypothermosol enhances MSC stability and preserves their functionality, suggesting its potential as an optimized storage solution for cell-based therapies. Additionally, the impact of cell concentration on viability underscores the importance of selecting appropriate dosing. Future studies should further investigate how these findings translate into clinical outcomes, particularly in terms of therapeutic efficacy and patient safety.